2015
DOI: 10.5194/aab-58-221-2015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acid–base balance as well as hematological and biochemical parameters in horses of combined driving discipline

Abstract: Abstract. The aim of this study was to evaluate the effect of training on hematological and biochemical blood indices and acid-base balance as well as to attempt an assessment of the degree of driving horses' training based on examined parameters during the training cycle. The study was conducted on eight Polish Halfbred driving horses (aged 6-12 years). Each four-horse harness included two geldings and two mares. Blood was collected before and directly after training as well as after a 30 min recovery period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Regardless of the scale of the effort and the type of exercise, in post-exercise studies an increase may be observed in the number of red blood cells, which is closely related to the increase in HGB and HCT (PICCIONE et al, 2008). A larger quantity of RBC is normal for horses that are trained properly (KUPCZYŃSKI and ŚPITALNIAK, 2015). In our study, a greater increase in RBC was found in group B after exercise.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Regardless of the scale of the effort and the type of exercise, in post-exercise studies an increase may be observed in the number of red blood cells, which is closely related to the increase in HGB and HCT (PICCIONE et al, 2008). A larger quantity of RBC is normal for horses that are trained properly (KUPCZYŃSKI and ŚPITALNIAK, 2015). In our study, a greater increase in RBC was found in group B after exercise.…”
Section: Discussionsupporting
confidence: 54%
“…Lactate concentration in the blood is a marker of anaerobic and aerobic thresholds during exercise in horses (ADAMU et al, 2014). The limit of anaerobic and aerobic thresholds amounting to 4 mmol/L (LINDNER et al, 2009) during exercise may have lower values for specific sports (KUPCZYŃSKI and ŚPITALNIAK, 2015). In both groups the LA concentration showed an increase after training, while in Group B, where additional physical stimulation was present, LA was lower than the resting values at the end of the sporting season.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The increase in the outlet of glucose after exercise is caused by the decrease in the insulin/glucagon ratio. High-performing horses are more capable of utilizing glucose than poor-performing ones [30]. The increase in glucose may be correlated with hyperactivity of the sympathetic system and activation of hepatic glycogenolysis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than training that influence horse driving scores Some studies consider the welfare and reactions to different stimuli in driving horses (Dziezyc et al 2011, Jahnke 1994, Kupczyński and Śpitalniak 2015. To the authors' knowledge, there is no study analyzing basic factors that influence sport results in the horse driving discipline.…”
Section: Introductionmentioning
confidence: 99%